Upaya Meningkatkan Penguatan Hafalan Al-Quran Penggunakan Metode Teman Sebaya Pada Mata Pelajaran Al-Quran - Eva Siti Faridah; Dul Rohman (AZKIA: Journal of Islamic Education in Asia, 2025)
This research is motivated by initial observations that showed low memorization scores among students in the Al-Qur'an subject. This can be seen from the students' average scores on daily test results, which ranged between 60-75 — still below the minimum mastery criteria (KKM). To improve Qur’an memorization, a classroom action was carried out by implementing the peer learning method. The purpose of this study is to examine the implementation of the peer learning method in enhancing students' memorization skills in the Al-Qur'an subject. This research also aims to determine how effective the peer method is in strengthening students' memorization abilities in the Al-Qur'an subject at SMP Muhammadiyah 1 Jakarta, and to assess how strong the students' memorization is when they recite to their teacher. The research method used is Classroom Action Research (CAR). The study was conducted in two cycles, each consisting of planning, action implementation, observation, and reflection. The subjects of this study were 30 eighth-grade students of SMP Muhammadiyah 1 Jakarta. The data collection techniques used in this research included observation, interviews, and documentation. Observation involved gathering data through memorization Q&A and oral examinations in which students recited their memorized verses. The results of this research include: 1. The implementation of the peer learning method in the Al-Qur'an subject was categorized as very good. 2. The students' memorization reinforcement in the Al-Qur'an subject showed improvement with each cycle using the peer learning method. It was found that, during the pre-cycle, the success rate percentage was 37%, which was below the minimum mastery criteria (KKM). After applying the peer method, in Cycle 1 the percentage increased to 70%, indicating an improvement of 33% from the pre-cycle. However, this was still below the expected percentage. Therefore, the next session proceeded with Cycle 2. After implementing Cycle 2, the percentage of memorization reinforcement increased to 80%, marking a 10% increase from Cycle 1. Thus, from pre-cycle to Cycle 2, the students' memorization improvement reached 43%. This percentage met the expected criterion of 75%. The implementation of the peer learning method can improve students' memorization reinforcement in the Al-Qur'an subject at SMP Muhammadiyah 1 Jakarta.